Socialist Practice - Wallis, Victor. author. aut Link
XX, 252 p.
Keywords: The level of popular discontent—in the United States as elsewhere—has shown a dramatic increase in recent years, but has yet to crystallize into a cohesive anti-capitalist political force. Socialist Practice aims to contribute to a popular movement for socialism. It does so by 1) revisiting, under present conditions, longstanding questions of Marxist theory and revolutionary history, and 2) illustrating the range of issues, activities, and forms of expression that can both inform and be informed by a Marxist approach. Essays spanning a range of national experiences address the crying need to generate a society-wide awakening, grounded in purposeful discussion among all those (the vast majority) whose interests are ill-served by continuation of the status quo. Victor Wallis is a professor in the Liberal Arts Department at the Berklee College of Music, USA, and was for twenty years the managing editor of Socialism and Democracy. He is the author of Red-Green Revolution: The Politics and Technology of Ecosocialism (2018) and Democracy Denied: Five Lectures on U.S. Politics (2019).